Photocatalytical Degradation of Methylene Blue using Laboratory Prepared Cadmium Sulphide - Dhungana, Kalpana; Rajbhandari, Armila (Journal of Nepal Chemical Society, 2025)
The cadmium sulphide (CdS) has been successfully synthesized in laboratory by chemical precipitation method. Cadmium chloride and sodium sulfide were used as precursor for the synthesis of CdS photocatalyst. The synthesized material was characterized by Fourier Transform Infrared Spectroscopy, X-ray diffraction, Scanning Electron Microscopy. The XRD peaks are obvious at 25.05, 26.9, 28.29, 43.9, 47.9, 52.07, 2θ degrees which indicates the crystalline phase of as prepared CdS material and average crystalline size was found to be 5.25 nm. Synthesized CdS nanoparticles were used to degrade the methylene blue (MB) dye under the irradiation of UV light. Different parameters like pH, concentration of MB dye, dose of CdS photocatalyst, UV irradiation time were evaluated. The preeminent pH of MB solution was found to be 9, the optimum catalyst dose was found to be 100 mg. Maximum 96% MB degradation was established when 1% of 1mL H2O2 was added along with 100 mg photocatalyst with continuous 210 minutes irradiation of UV light. The H2O2 provides sufficient •OH radicals and upsurges the efficiency of CdS photocatalyst. The results revealed that laboratory prepared CdS nanoparticles could be a good material to use as a photocatalyst for the degradation of cationic dye like MB.